Blood Biomarkers of Sports-Related Concussion in Pediatric Athletes. Issue 3 (May 2021) - Anzalone, Anthony J.; Turner, Stephanie M.; Baleztena, Angela C.; McGuffin, Tiffany; Creed, Kalyssa; Jeromin, Andreas; Wilson, David; Hanlon, David; Garrison, J. Craig; Blueitt, Damond; Oliver, Jonathan M.
Abstract : Objective: To examine changes in blood biomarkers, serum neurofilament light (Nf-L), and plasma tau, as well as the relationship between blood biomarkers and symptom reports, in athletes with a sports-related concussion. Design: Prospective cohort study. Setting: Private community-based concussion clinic. Participants: Athletes aged 13 to 18 years old with a diagnosed sports-related concussion presenting to a concussion clinic within 7 days of injury and noninjured athletes with no history of concussion aged 13 to 23 years old. Assessment and Main Outcome Measures: Injured athletes provided a blood sample at the initial clinical evaluation and again at least 6 months after injury. Noninjured athletes provided a single blood sample. All participants completed symptom reports during each visit. Statistical comparisons of biomarker concentrations and symptom reports were conducted. Results: The mean rank for tau was significantly lower for concussed athletes compared with nonconcussed athletes. In contrast, the mean rank of Nf-L was higher for concussed athletes than for nonconcussed athletes, although the difference was nonsignificant. Plasma tau was significantly lower postinjury compared with 6 months after injury, whereas serum Nf-L was significantly higher postinjury. There was a weak but significant inverse relationship observed between tau and the number of symptoms reported, but no relationship was observed between Nf-L and the number of symptoms reported. Conclusions: These data indicate that in the days following a sports-related concussion, the blood biomarkers tau and Nf-L display contrasting patterns of change but may not be related to self-reported symptom scores.